RESPONSE OF GREEN BEANS (Vigna radiata L.) GERMINATION ON LEAVES AND RHIZOMES COGONGRASS (Imperata cylindrica L.) ALLELOPATHY - Sari, Heni Erlita; Mahfut, Mahfut (Fakultas Sains dan Teknologi, Universitas Islam As-Syafi'iyah, 2023)
Cogongrass is a plant that contains allelochemicals, so it has the capability to reduce viability and early growth in green bean germination. This study aimed to determine the effect of allelopathy extract on the size and number of root cells in mung bean sprouts. The study uses the Completely Randomized Design with 1 treatment and 5 concentration levels of reed extract and repeated twice. The concentrations of the reeds used were 0% (control), 25%, 50%, 75%, and 100%. The results showed that high concentrations of Cogongrass allelopathic extract inhibited the growth of soybean sprouts based on plant length. Each concentration of reed extract did not show a significant difference in cell length or cell density of mung bean sprouts.